EMBEDDEDNESS OF CSR MANAGEMENT AND THE KING’S KNOWLEDGE ENDORSEMENT AFFECTING CUSTOMER SUPPORT - Tacheorn, Srisuda; Piriyakul, Rapepun; Khantanapha, Napaporn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
To be successful for Social Business Enterprise, the economic, social and environmental value must be balancing based on the effectiveness of Strategic Human Resource Management, and Corporate Governance. From the empirical study, it was found that the managing dominant features of Doi Kham were the Embeddedness of Corporate Social Responsibility Culture and King’s Knowledge Endorsement. This study was conducted by using 300 sampling units from Thai people with age 17 – 35 years in Bangkok Metropolis. The theoretical conceptual framework consisted of 2 independent factors: The Embeddedness of Corporate Social Responsibility Culture (ECR) and the King’s Knowledge Endorsement (KKE); 2 intermediate factors: Corporate Image Perception (CP) and Mutual Gain Perception (MGP); and Customer Support as the dependent factor. It was found that the average value of all factors was the high level of awareness. The hypothesis testing found that ECR and KKE had a positive significant influence on CP and MGP with coefficient values of 0.643, 0.722, 0.589 and 0.289, respectively.